The onset of soret driven ferrothermoconvective instability in the presence of darcy porous medium with anisotropy effect and MFD viscosity - Murugan, D.; Sekar, R. (Zielona Góra: Uniwersytet Zielonogórski)
The effect of magnetic field dependent (MFD) viscosity on Soret driven ferrothermohaline convection in a densely packed anisotropic porous medium has been studied. The Soret effect is focused on the system. A linear stability analysis is carried out using a normal mode technique and a perturbation method is applied.
Keywords: anisotropy effect; Darcy model; MFD viscosity; porous medium; Soret coefficient